THE USE OF CAROUSEL FEEDBACK IN ORDER TO IMPROVE STUDENT PERSONAL RELATIONSHIPS TAKING PART A VILLAGE VOCATIONAL PROGRAMME CONCERNED WITH STARFRUIT FARMING IN DEPOK (A DISTRICT OF WEST JAVA) - Anwar, Saiful (Faculty of training and education, Pamulang university, 2016)
: Carousel feedback is a method of teaching that focuses on developing personal relation-ships (social & communication skills) as well as akademic skills (analytical, knowledgebuilding & presenting skills). It is used to solve problems of ?the shringking violets & bulles? in entrepreneur-ship classes. This research employed a qualitative in classroom action research. Data was collected by using observation sheets, questionaires, fields notes and photos, the subjects were 20 undergra-duates of the S1 Economic Education Program FKIP Universitas Pamulang (especially those en-rolled in the vocational village programme at Rangkapan Jaya subdistric, and Pancoran Mas distrik, Depok, West Java). Analyses of the data obtained indicated that: 1) Carousel feedback method could be used to instil entrepreneurship; 2) students response was varied; 3) social and communica-tion skills improved. Study problems: 1) coordinating time schedules between village and univer-sity; 2) lack of self confidence in students especially in those from Java. Keywords: Carousel feedback, social skills, communication skills, analytical skills, vocational village